2020
DOI: 10.1111/odi.13366
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of neutrophil‐to‐lymphocyte ratio in HPV status era for oropharyngeal cancer

Abstract: Aim To evaluate the role of baseline neutrophil‐to‐lymphocyte ratio (NLR) as prognostic marker in squamous cell carcinoma of the oropharynx (OPC) treated with definitive chemoradiotherapy (CRT) in the era of HPV status. Patients and methods A retrospective analysis of 125 patients (pts) affected with locally advanced OPC was performed. Inclusion criteria were age >18 years, stage III or IV (TNM 7th ed.) and definitive CRT. Haematological marker for their independent role as prognostic biomarkers for progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Three other studies assessing the NLR reported prognostic significance, but dichotomized NLR values solely on the sample median. [29][30][31] Furthermore, in two studies, event rates were low and CIs were large, 30,31 and in the other, 45% of patients received induction chemotherapy, potentially confounding results. 29 Strengths of our study were the larger sample size, including discovery and validation cohorts, excluding cases treated with induction chemotherapy, and analyzing ALC as a continuous variable.…”
Section: Discussionmentioning
confidence: 96%
“…Three other studies assessing the NLR reported prognostic significance, but dichotomized NLR values solely on the sample median. [29][30][31] Furthermore, in two studies, event rates were low and CIs were large, 30,31 and in the other, 45% of patients received induction chemotherapy, potentially confounding results. 29 Strengths of our study were the larger sample size, including discovery and validation cohorts, excluding cases treated with induction chemotherapy, and analyzing ALC as a continuous variable.…”
Section: Discussionmentioning
confidence: 96%
“…As a consequence, unlike other studies reporting an association between a high NLR and poor outcome in HNSCC 2 and laryngeal cancer, 21 this ratio was not associated with outcome in the present series. However, other authors have failed to identify an association between preoperative NLR and DFS both in laryngeal 22 and oropharyngeal SCC 23 . Interestingly, in a series of patients with HNSCC, it was observed that the prognostic capability of NLR mostly depended on the number of neutrophils with the lymphocytes contributing limitedly 2 .…”
Section: Discussionmentioning
confidence: 97%
“…However, other authors have failed to identify an association between preoperative NLR and DFS both in laryngeal 22 and oropharyngeal SCC. 23 Interestingly, in a series of patients with HNSCC, it was observed that the prognostic capability of NLR mostly depended on the number of neutrophils with the lymphocytes contributing limitedly. 2 In this regard, it should also be considered that use of steroids is more frequent in laryngeal cancer, to reduce oedema and improve breathing, and possibly associated with a transient increase in neutrophil count.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of circulating peripheral blood neutrophils in relation to lymphocytes has been suggested as a potential prognostic marker for many cancers including OPSCC [ 43 , 44 ]. A high circulating neutrophil to lymphocyte ratio (NLR) has been found for both HPV-positive and HPV-negative OPSCC [ 45 ]. In HPV-positive OPSCC, a high NLR was associated with higher T classification, lower 5-year overall survival and disease-free survival [ 46 ].…”
Section: Discussionmentioning
confidence: 99%